Status and Conservation of the Saker Falcon in Austria - Johannes A. Hohenegger; Karin E. Donnerbaum; Richard Zink; Hans-Martin Berg (Пернатые хищники и их охрана)
The short lecture summarizes the results of a conservation program for the Saker Falcon (Falco cherrug) in Austria for the years 2011–2022. The species reaches the western limit of its global distribution in Austria. Therefore, it is restricted to the east of the country and naturally a scarce species with high conservation concern.